"In-water" direct arylation polymerization (DArP) under aerobic emulsion conditions. Issue 46 (16th November 2021) - Ye, Liwei; Hooshmand, Tanin; Thompson, Barry C.
Abstract : To address the issue of generating large amounts of organic waste from conjugated polymer synthesis, the first direct arylation polymerization (DArP) protocol under emulsion conditions is disclosed with a 10-fold reduction of organic solvent utilized. Abstract : Despite limited reports employing sustainable solvents for Direct Arylation Polymerization (DArP), the large amount of organic waste generated from conjugated polymer synthesis requires attention. Herein, we report the first emulsion-DArP methodology to afford polymers with molecular weights up to 14.5 kg mol −1 with a 10-fold reduction of organic solvent utilized.